Outcome after Combined Lateral Extra-articular Tenodesis and Anterior Cruciate Ligament Revision in Professional Soccer Players - Alessio-Mazzola, Mattia; Formica, Matteo; Russo, Antonio; Sanguineti, Francesca; Capello, Andrea Giorgio; Lovisolo, Stefano; Felli, Lamberto (The Journal of Knee Surgery, 2019)
We report the functional outcome after combined anterior cruciate ligament (ACL) reconstruction and lateral extra-articular tenodesis (LET) for ACL re-rupture and high-grade pivot shift in professional soccer players. For this retrospective review, the medical records of 24 professional soccer players were analyzed. The mean age at surgery was 23.8 ± 4.2 years and the mean follow-up was 42.2 ± 16.9 months. Pre- and postoperative assessment included the KT-1000 Lachman test, pivot shift test, International Knee Documentation Committee (IKDC) subjective knee evaluation, Tegner activity scale (TAS), and Lysholm score. The rate of return to sports and the level of play at final follow-up were recorded. ACL revision was performed with an autologous bone–patellar tendon–bone autograft or a hamstring graft. LET was performed using an extra-articular MacIntosh procedure as modified by Arnold–Coker. Anterior–posterior laxity was significantly reduced at the final clinical assessment (p < 0.0001): 22 patients (91.7%) had a negative pivot shift and 2 (8.3%) had residual glide (+), with significant improvement (p < 0.0001). The mean subjective IKDC and Lysholm score improved from 69.5 ± 11.1 (range: 56–90) to 88.4 ± 8.9 (range: 62.1–100) and from 58.1 ± 11.7 (range: 33–72) to 97.4 ± 3.2 (range: 88–100), respectively, with significant improvement (p < 0.0001) over preoperative values. The overall failure rate was 8.3%. There were no differences between mean preinjury and final TAS scores (p > 0.05). The rate of return to sports at the same level was 91.7% and the mean time to return to sports was 9.2 ± 2.2 months. Mid-term functional outcome after combined extra-articular reconstruction and ACL revision surgery was satisfactory, with a reduction in residual postoperative rotatory instability and degree of pivot shift.
Keywords: ACL reconstruction; lateral extra-articular tenodesis; knee rotational instability; ACL revision; Arnold–Coker; MacIntosh